Noise-Induced Hearing Loss in the Police Force - Kyaw N. Win; Nayake B.P. Balalla; Min Z. Lwin; Alice Lai (Elsevier, 2015)
Background: Noise-induced hearing loss (NIHL) is a major preventable occupational health problem with 250 million people worldwide known to have disabling impairment of moderate to greater severity. The aims of the study are to estimate the prevalence of NIHL in the police force; and study its association with age, sex, duration of service (years), smoking and alcohol habits, use of hearing protective devices, as well as preexisting chronic diseases. Methods: A cross-sectional study was conducted on 543 police personnel who had undergone periodic medical examination over a 12-month period. The diagnostic criteria for NIHL were (1) history of occupational noise exposure, (2) bilateral hearing loss, (3) hearing loss of ≥ 25 dBA at 4,000 Hz in two consecutive audiograms, and (4) no significant medical history affecting hearing. Severity of NIHL was based on the World Health Organization grading. Results: Males (74.8%) made up the majority of the police force. The mean age for police personnel was 35.55 ± 9.57 years, and the mean duration of service was 14.75 ± 9.39 years. Compliance with the usage of hearing protective devices was seen in 64.4%. The prevalence of NIHL in this study population was 34.2%, with a higher prevalence in males (37.7%) than in females (23.9%). The study also showed strong associations between NIHL and male sex (odds ratio, 1.9; P < 0.05), and hypertension (odds ratio, 3.3; P < 0.001). Overall, 93% were found to have mild NIHL, 3.5% had moderate NIHL, and 3.5% had severe NIHL. No police personnel were found to have profound hearing loss. Conclusion: The prevalence of NIHL in this study is high compared to other similar studies among police personnel. This study shows that increasing age, male, presence of hypertension, diabetes, and longer duration of service are significant associated factors for NIHL. Preventative strategies include health surveillance, implementation of a hearing conservation program, and legislation.